Indonesia's Contested Norms, Selective Humanitarianism and ASEAN Refugee Governance - Prabandari, Atin; Segara, Balya A.; Ketaren, Emma Seruni (Nation State: Journal of International Studies, 2025)
This article reinterprets Indonesia’s refugee governance and ASEAN’s regional approach as sites of norm contestation rather than mere institutional or capacity gaps. While the 1951 Refugee Convention promotes universal protection, Southeast Asia largely avoids fully integrating these norms. Indonesia exemplifies this paradox: it champions humanitarian diplomacy in forums like the Bali Process. It offers ad-hoc aid during crises, such as the 2015 Rohingya influx, yet it simultaneously upholds a restrictive asylum policy and remains outside key international refugee agreements. ASEAN, similarly, resists formalizing refugee protection, adhering to its core tenets of non-interference, informal regionalism, and consensus. Drawing on regionalism, securitization, and postcolonial theories, the article argues these are not failures, but deliberate political choices driven by concerns of sovereignty, security, and normative pluralism. It reveals how Southeast Asian refugee governance stems from conflicting regional identities and historical legacies, fostering a fragmented landscape where humanitarianism becomes a selective political tool. This analysis enriches critical discussions on refugee protection in the Global South and highlights the limitations of liberal humanitarian norms in diverse postcolonial contexts.